Korelasi Kepadatan Banggai Cardinal Fish (Pterapogon kauderni) dengan Biota Asosiasi (Diadema setosum dan Fibramia thermalis) di Perairan Teluk Gilimanuk, Bali - Stephanus Tambunan; I Wayan Arthana; I Nyoman Giri Putra (Journal of Marine Research and Technology, 2022)
Banggai cardinal fish (Pterapogon kauderni) is a marine fish native to Indonesia. P. kauderni is listed as an endangered species in the red list category by the IUCN. P. kauderni is very dependent on microhabitats in the form of benthic animals (symbionts), namely sea urchins, sea anemones, and hard corals. Besides P. kauderni, other fish from the family Apogonidae also live in association with sea urchins. The purpose of this study was to examine the density of P. kauderni and associated biota and to calculate the density correlation between P. kauderni associated biota in the waters of Gilimanuk Bay, Bali. This study uses a modification of the Belt Transect method, with a transect of 50 meters long and 2.5 meters wide to the left and right. The total density of sea urchins was 0,088 ind/m2, the total density of Fibramia thermalis was 0,021 ind/m2, and the total density of P. kauderni was 0,071 ind/m2. Between P. kauderni and sea urchins there is a correlation with the value of r = 0,711 and a P-value of 0,031 < 0,05 which indicates that the large number of sea urchins will affect the number of P. kauderni in the waters. The correlation between density of P. kauderni and Fibramia thermalis worth r = 0,509 with P-value of 0,160 > 0,05, which means that the number of Fibramia thermalis has no effect on the number of P. kauderni.